Peculiarities and asymmetry of polarization reversal in Pt/PZT-film/Pt:Ti/SiO₂/Si-substrate structures in pyroelectric response investigations - Bravina, S.L.; Cattan, E.; Morozovsky, N.V.; Remiens, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
By RF magnetron sputtering method the Pt/PZT-film/Pt:Ti-sublayer/SiO₂/Si-substrate structures were prepared and pyroelectric response amplitude and phase behaviour under external voltage application was investigated by photopyroelectric modulation method.
The results of investigation of pyroelectric response – external voltage loops of polarization reversal, pyroelectric response – voltage poling curves and pyroelectric response – time repolarization curves and also dynamic current-voltage characteristics of Pt/PZT/Pt:Ti/SiO₂/Si-substrate structures are presented.
From variation of pyroelectric response in the current and voltage modes the capacity-voltage loops of polarization reversal and poling curves were derived. From asymmetric pyroelectric response – time repolarization curves the voltage behaviour of characteristic times of zero response and saturation was analyzed. Observed transformations of current-voltage characteristics display the considerable voltage and time dependent variation of charge transfer conditions.
The performed investigation has shown the strong correlation between the poling pyroelectric and so ferroelectric and electrical asymmetries. Presented data on the polar and time asymmetry of the conditions of polarization reversal are discussed in the terms of influence of dynamics of space charge asymmetry on pinning conditions under the different polarity of applied voltage in the course of polarization reversal.